Increased PSNR with improved DWT digital watermarking technique. (30th October 2019) - Khan, Ifra I.; Ahmad, Khaleel; Rizvi, M.A.; Ahmad, Khairol Amali Bin
Today, the world is moving towards a digital era in every walk of life. Every business, government and private sectors, and research organisation use the digital image, as a transfer mode for critical data. The images over the internet are not secure therefore, image security is needed. In this work, a new technique of image security is proposed using digital watermarking which is more efficient and robust than the discrete wavelet transform (DWT). The whole mechanism is greatly reliable on the human visual system, as the watermark is not visible to the human eye. This increases the security of the hidden image or messages. The technique is tested against the PSNR of several images. The average PSNR calculated of all the tested images was compared to other techniques and found that the new technique is better than the existing techniques. This technique can be used for security of multimedia data.